The effect of external factors on dielectric permittivity of Rochelle salt: humidity, annealing, stresses, electric field - Slivka, A.G.; Kedyulich, V.M.; Levitskii, R.R.; Moina, A.P.; Romanyuk, M.O.; Guivan, A.M. (Condensed Matter Physics, 2005)
The effect of external factors, such as dessicating/wetting, thermal annealing, uniaxial and hydrostatic pressure, on the dielectric permittivity of Rochelle salt crystals is investigated. The obtained results are compared with the available literature data and analyzed within the phenomenological Landau approach. A significant effect of the internal polar point defects in crystals and storage conditions on the dielectric permittivity is shown.